THE ROLE OF WOMEN IN THE MAENGKET DANCE BASED CREATIVE ECONOMY IN MINAHASA: A STUDY OF INCOME AND WELL-BEING: Peran Perempuan dalam Ekonomi Kreatif Berbasis Tari Maengket di Minahasa: Studi Pendapatan dan Kesejahteraan - Morshe Everly Lumansik; James Edward Lalira; Lucky Paulus Tumbelaka (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
Abstract This study examines the role of women in the Maengket dance-based creative economy in Minahasa, North Sulawesi, focusing on their economic contributions, welfare outcomes, and the structural challenges they face. Employing a mixed-methods design, data were collected through surveys with 20 female practitioners, in-depth interviews, focus group discussions, and participant observation. The findings reveal that while women constitute the core workforce in Maengket performance, costume production, and training, their economic recognition remains limited. Most respondents are young (19–35 years), educated (75% at least high school graduates), and have been involved for over three years, yet average annual income from performances ranges between IDR 390,000 and IDR 520,000—far below regional living standards. Income instability, lack of formal financial systems, and exclusion from decision-making processes underscore their marginalization in the value chain. Despite the high demand for cultural performances nationally and internationally, women face barriers, including limited digital literacy, minimal access to capital, and male-dominated event management structures. Thematic analysis highlights the dual burden of cultural and domestic responsibilities, as well as aspirations for entrepreneurship, digital marketing, and collective economic models such as cooperatives. The SWOT analysis further identifies strong cultural capital and networked studios as strategic assets, while dependence on government events, weak branding, and insufficient innovation constrain sustainability. This study contributes to the literature on gender and creative economies by demonstrating how cultural production, despite being central to identity and tourism, often fails to translate into equitable economic outcomes for women. This calls for inclusive policies that integrate financial inclusion, digital empowerment, and gender-responsive cultural governance. The study concludes that the sustainable development of traditional arts requires not only cultural preservation but also the formal recognition and economic empowerment of women as key agents of the creative economy.